'The New Degree?' Constructing Internships in the Third Sector. (April 2016) - Leonard, Pauline; Halford, Susan; Bruce, Katie
The recent economic recession has impacted substantially on the graduate labour market, with many graduates now struggling to find secure employment in professional careers. In this context, temporary, unpaid 'internships' have emerged as increasingly important as a 'way in' to work for this group. Yet while there has been much media and policy debate on internships, academic consideration has been scant. This article begins to address this knowledge gap by drawing on a study of interns in a third sector environmental organisation. The research findings reveal that unpaid internships were rationalised through a complex mix of political motivations, career ambitions and lifestyle aims, but these intersected in important ways with social class. These findings are not only of empirical interest, contributing to our knowledge of graduate negotiations of precarity, but also of theoretical value, extending our understanding of young people's agency and motivations in transitions into work.